Integrasi Hukum Adat dalam Kerangka KUHP Baru: Evaluasi Pluralisme Hukum dan Tantangan Implementasi Restoratif Justice - Wahyudhi, Dheny; Herlambang, Herlambang; Sudarti, Elly (Indonesian Journal of Law and Justice, 2025)
The integration of customary law within the framework of the new Criminal Code (KUHP) places normative pluralism as a strategic issue for national law reform. This article aims to evaluate the extent to which recognition of customary norms is in line with the principles of restorative justice proposed in the new Criminal Code and to identify implementing barriers at the level of legislation, judicial practice, and indigenous communities. The research approach is juridical-normative, combining doctrinal studies, analysis of legislative texts, and reviews of decisions and related policies. The results of the analysis show that although the new Criminal Code framework opens up the possibility of recognizing customary norms through alternative solutions, there is an unclear recognition criteria, procedural inconsistencies, and the risk of subordination of customary norms by state rules. Furthermore, limited institutional capacity and disparities in access to legal representation hinder the realization of participatory restorative justice principles. In conclusion, effective integration requires clear normative differentiations, participatory verification mechanisms, and strengthening the capacity of judicial institutions and indigenous communities. Legal implications include the need for technical amendments and implementation guidelines to ensure harmonization between legal pluralism and restorative justice goals. Practical recommendations include customary verification standards, training of cultural mediators, and independent monitoring mechanisms to assess compliance with restorative justice principles.